Innovative National and International Experiences Compared between Memory and Amnesia (diségno, 2024)
The UID Symposium on Internationalization and Innovation of Research is part of the Days of Restoration and Cultural Heritage 2024 and aims to promote the internationalization of research and its constant innovation.Held in Ferrara on March 19, 2024, the conference aimed to give continuity to the events of previous years to promote research at the international level and to present the roadmap of the work of the Innovation Commission, starting from the strategic areas of development that include the themes of Digitization, Visualization and Social Innovation for the enhancement of Cultural Heritage, the conservation of the built, historical, and artistic heritage, and the contexts of city, territory, landscape and environment. [read more]